Association between traditional fermented milk (mursik) consumption and oesophageal carcinoma among patients presenting to two referral hospitals in Nandi County, Kenya: A case-control study - Rancy Chepkoech Mutai; Marshal M. Mweu (PLoS ONE, 2025)
Background Oesophageal carcinoma (OC) is a prominent cause of morbidity and mortality in low and middle-income countries yet little evidence exists about its contextual drivers. The objectives of this study were to assess the association between traditional fermented milk (FM) (mursik) consumption and OC independent of known socio-demographic and lifestyle risk factors as well as to quantify its population impact among patients presenting to two referral hospitals in Nandi County, Kenya. Methods A hospital-based case-control study was employed to assess the FM-OC relationship among patients presenting to Kapsabet Surgical Care Centre and Kapsabet County Referral Hospital in Nandi County, Kenya for care between 23rd November 2023 and 13th January 2024. All 33 cases meeting specific eligibility criteria were prospectively recruited whilst 131 controls were simple randomly sampled and frequency-matched to the cases by hospital and day of presentation. A logistic regression model was fitted to assess the FM-OC association while adjusting for potential confounders. Subsequently, a population attributable fraction (PAF) for the association (along with its confidence interval) was estimated. Results A strong association between FM and OC was noted; the odds of OC among frequent and infrequent consumers of FM being over nine (OR 9.1, 95% CI: 3.1–26.6) and three (OR 3.2, 95% CI: 1.1–9.2) times higher, respectively, than non-consumers. This association was not substantially confounded by the studied socio-demographic and lifestyle factors. The PAF estimate for this association was 65.2% (95% CI: 40.1–90.7). Conclusions In this study setting, mursik consumption was strongly associated with OC independent of other risk factors. This association registered a high PAF suggesting that up to 65% of OC in the population could be prevented if mursik was not consumed. This finding calls for safe, community-owned alternatives for fermenting milk in order to mitigate the risk of OC in this population.